External Debt, Savings and Growth in Latin America : Papers Presented at a Seminar Sponsored by the International Monetary Fund and the Instituto Torcuato di Tella, held in Buenos Aires on October 13-16, 1986. (International Monetary Fund, 1987)
Edited by Ana Maria Martirena-Mantel, this volume, published in Spanish and English, contains the papers presented at a seminar sponsored jointly by the IMF and the Instituto Torcuato di Tella of Argentina. The seminar was held in Don Torcuato, near Buenos Aires. The volume consists of six papers, commentaries, and an overview by the editor, who also acted as moderator at the seminar.